Extending the NegEx lexicon for multiple languages - Chapman, Wendy W; Hillert, Dieter; Velupillai, Sumithra; Kvist, Maria; Skeppstedt, Maria; Chapman, Brian E; Conway, Mike; Tharp, Melissa; Mowery, Danielle L; Deleger, Louise (Medinfo 2013 : proceedings of the 14th World Conference on Medical and Health Informatics, 2013)
We translated an existing English negation lexicon (NegEx) to Swedish, French, and German and compared the lexicon on corpora from each language. We observed Zipf's law for all languages, i.e., a few phrases occur a large number of times, and a large number of phrases occur fewer times. Negation triggers "no" and "not" were common for all languages; however, other triggers varied considerably. The lexicon is available in OWL and RDF format and can be extended to other languages. We discuss the challenges in translating negation triggers to other languages and issues in representing multilingual lexical knowledge.